Answer with Step-by-step explanation:
We are given that
![x^2+y^2=(\sqrt 2)^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/q40oedfp0665mpdz6i6ddatwoynpdpeay2.png)
![(x-3)^2+(y-3)^2=32=(4\sqrt 2)^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/an1qmhmfhpqgq03e17pei0broo879qfy2f.png)
Compare with the equation of circle
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3gezmntbbjw0kxpks4y5gde90ue9dh956u.png)
Where center of circle=(h,k)
r=Radius of circle
a.Center of circle=(0,0)
Radius=
units
Center of second circle=(3,3)
Radius of second circle=
units
b.Distance formula:
![\sqrt{(x_2-x_1)^2+(y_2-y_1)^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/ghhzuhlxbim60vz8xka92ctz40dwlrqb4m.png)
Using the formula
The distance between the centers of two circle
=
![√((3-0)^2+(3-0)^2)=3\sqrt 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/n3d6kpjhm6vcflat613v0gcpoyd98w2cx8.png)
Hence, the distance between the centers of two circle =
units.
c.
Substitute x=-1 and -1
![1+1=2=](https://img.qammunity.org/2021/formulas/mathematics/high-school/qwiegmwdcyjwre2so2zao1bgf6h678ywiv.png)
![(1-3)^2+(1-3)^2=32](https://img.qammunity.org/2021/formulas/mathematics/high-school/xlc9l5uqaouoafvy4sv3l0dbcqg9jo1ods.png)
The circle must be tangent because there is just one point (-1,-1) is common in both circles and satisfied the equations of circle.